2014
DOI: 10.1371/journal.pone.0089692
|View full text |Cite
|
Sign up to set email alerts
|

School Based Sex Education and HIV Prevention in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis

Abstract: ObjectivesSchool-based sex education is a cornerstone of HIV prevention for adolescents who continue to bear a disproportionally high HIV burden globally. We systematically reviewed and meta-analyzed the existing evidence for school-based sex education interventions in low- and middle-income countries to determine the efficacy of these interventions in changing HIV-related knowledge and risk behaviors.MethodsWe searched five electronic databases, PubMed, Embase, PsycInfo, CINAHL, and Sociological Abstracts, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(219 citation statements)
references
References 90 publications
(175 reference statements)
7
203
5
4
Order By: Relevance
“…Although our results suggest high school sex education does not improve condom use confidence, overseas literature supports its efficacy. A meta-analysis comparing students participating or not participating in school-based sex education showed those who received education had significantly greater self-efficacy relating to condom use, more frequent condom use, and fewer sexual partners ( P < 0.001) [29]. Contrary to the findings of our study, the result of this meta-analysis suggests that condom efficacy can be improved independently of sexual experience, which is promising for high school educational intervention.…”
Section: Discussioncontrasting
confidence: 87%
“…Although our results suggest high school sex education does not improve condom use confidence, overseas literature supports its efficacy. A meta-analysis comparing students participating or not participating in school-based sex education showed those who received education had significantly greater self-efficacy relating to condom use, more frequent condom use, and fewer sexual partners ( P < 0.001) [29]. Contrary to the findings of our study, the result of this meta-analysis suggests that condom efficacy can be improved independently of sexual experience, which is promising for high school educational intervention.…”
Section: Discussioncontrasting
confidence: 87%
“…[29][30][31][32] However, poor implementation of schoolbased programs at scale, including problems of curricula lacking basic information on condoms and contraception, poor teaching, and short program durations, have often resulted in a lack of fidelity to the designed intervention, reducing program effectiveness. 33 Our study supports the idea that text-messaging programs may be effective ways to fill this gap, by providing accurate and complete information via a medium with which adolescents are comfortable.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…There have been a large number of systematic reviews that evaluated the effectiveness of these programmes (Chin 2012; Dick 2006; DiClemente 2008; Flisher 2008; Gallant 2004; Harrison 2010; Johnson 2003; Johnson, 2011; Kim 2008; Kirby 2007; Lazarus 2010; Magnussen 2004; Medley 2009; Michielsen 2010; Paul 2008; Shepherd 2010; Yankah 2008), including reviews that have focused solely on school-based interventions (Bennet 2005; Fonner 2014; Kirby 2006; Lopez 2016; Paul 2008), and a review of reviews (Mavedzenge 2013). Many of these reviews have suggested that school- and community-based prevention programmes for adolescents have been effective in delaying self-reported sexual activity, HIV-related preventative behaviours, adolescent pregnancy, and STIs (Chin 2012; Fonner 2014; Johnson 2003; Johnson, 2011; Kirby 2009; Laud 2016), although others have reported less, or mixed, success (Bennet 2005; DiCenso 2002; Lopez 2016 Oringanje 2016). The logic model for how these programmes might be thought to influence sexual and reproductive health outcomes can be seen in Figure 1.…”
Section: Introductionmentioning
confidence: 99%